Πρότυπα παιδείας στον ελληνόφωνο χριστιανικό κόσμο:Από την πρωτοχριστιανική περίοδο μέχρι την Άλωση - Efstathios Lianos-Liantis (The Eusebius Lab International Working Papers Series, 2020)
From the very beginning of the establishment of the Church, education and peda-gogy had beenat the epicenter of the thought of great theologians and Christian philosophers as anthropomorphic ideals, which civilization offers to societies in order to form complete and integrated personalities capable to understand the truth about life, the world,and their place in it. The Church Father’s knowledge is based on Divine Wisdom which they passed to the community of believers in proclamations, preaching, witnessing and which was also shared at the gathering of worshiping communities.